A Lógica, o Nonsense e a filosofia da lógica de Lewis Carroll - Lindemann, John Lennon (2021)
This thesis is divided into four articles, covering different aspects of Lewis Carroll's Logic and Philosophy of Logic. The first article reproduces three paradoxes presented by Lewis Carroll, and it examines how Carroll, from his logical tooling, treated such paradoxes compared to the treatment offered by other authors. The article reproduces the controversy between Lewis Carroll and John Cook Wilson about the nature of the implication, concluding that Carroll defended a position congruent with the verifunctional interpretation of the notion of implication adopted by contemporary logicians. The second article investigates whether the essential characteristics that define the Smullyan's Tree Method were already present, about 50 years earlier, in the Carroll's Tree Method. After reconstruction of the history of the development of the tableaux method and the analysis of the essential characteristics of both authors methods, including a comparison of examples of their applications, we conclude that the characteristics that define the Smullyan's Trees were already present in Carroll's Trees, in such a way that, for historical justice, the method should be known as "Carroll-Smullyan's Trees." This conclusion highlights the significant Carrollian contribution to the development of Logic, demonstrating the relevance of an investigation into the author's position in the Philosophy of Logic. The third article presents a notion of nonsense appropriate to Carroll's works and derived from his theoretical framework, concluding that Carroll used nonsense as a means of inducing instructive ideas in his readers. The article also compares Carroll and Wittgenstein's nonsense notion and argues that the two authors had similar attitudes towards nonsense. The fourth article presents an original hypothesis about Carroll's Philosophy of Logic, stating that Carroll defended a position analogous to the current pragmatic position.